Novel pyridone EP4 agonists featuring allylic alcohol ω-chains. Issue 10 (15th May 2020) - Dorich, Stéphane; Cox, Jennifer H.; Burch, Jason D.; Chagnon, Félix; Chen, Bin; Léger, Serge; St-Onge, Miguel; Fader, Lee D.
Graphical abstract: Abstract: Novel prostaglandin E2 receptor 4 (EP4 ) agonists featuring a pyridone core and an allylic alcohol ω-chain were discovered. These agonists were shown to be selective over EP1, EP2 and EP3 . Analogs harboring a 4-carboxylic acid phenethyl α-chain displayed improved potency over those containing an n -heptanoic acid chain. Key SAR relationships were also identified.